Differing visions of a learning society : research findings. - Coffield, Frank (Policy Press, 2000)
This first volume explores the ways lifelong learning can contribute to the development of knowledge and skills for employment, and other areas of adult life. It addresses the challenges to social science researchers to study issues that are central and directly relevant to the political and policy debate, and to take into account the reality of people's lives.
Published in association with the ESRC Learning Society Programme.
Keywords: Continuing education.; Vocational education.; Education, Continuing; Vocational Education; Éducation permanente.; Enseignement professionnel.; continuing education.; EDUCATION -- Adult & Continuing Education.; EDUCATION -- Non-Formal Education.; EDUCATION -- Educational Policy & Reform -- School Safety.; Continuing education; Vocational education; Electronic books.